2023
DOI: 10.1001/jamanetworkopen.2022.56186
|View full text |Cite
|
Sign up to set email alerts
|

Association of Accelerometer-Measured Physical Activity Level With Risks of Hospitalization for 25 Common Health Conditions in UK Adults

Abstract: ImportanceHigher physical activity levels are associated with lower risks of cancer, cardiovascular disease, and diabetes, but associations with many common and less severe health conditions are not known. These conditions impose large health care burdens and reduce quality of life.ObjectivesTo investigate the association between accelerometer-measured physical activity and the subsequent risk of hospitalization for 25 common reasons for hospitalization and to estimate the proportion of these hospitalizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In addition, the NAVIGATOR study [ 94 ], which includes 9,000 individuals with high cardiovascular risk or impaired glucose tolerance, showed that for every increase of 2000 steps per day, the risk of developing cardiovascular problems decreased by 10%, the risk of developing type 2 diabetes mellitus (T2DM) by 5.5%, and the metabolic syndrome risk score was reduced by 0.29 [ 94 – 96 ]. A recent large cohort study on 81,717 participants showed that an increase of 20 min in daily MVPA is associated with a reduction in hospitalization ranging from 3.8% for colon polyps, 14.1% for pneumonia, 19.8% for gallbladder disease, 22.7% for urinary tract infection, and 23% for diabetes [ 97 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NAVIGATOR study [ 94 ], which includes 9,000 individuals with high cardiovascular risk or impaired glucose tolerance, showed that for every increase of 2000 steps per day, the risk of developing cardiovascular problems decreased by 10%, the risk of developing type 2 diabetes mellitus (T2DM) by 5.5%, and the metabolic syndrome risk score was reduced by 0.29 [ 94 – 96 ]. A recent large cohort study on 81,717 participants showed that an increase of 20 min in daily MVPA is associated with a reduction in hospitalization ranging from 3.8% for colon polyps, 14.1% for pneumonia, 19.8% for gallbladder disease, 22.7% for urinary tract infection, and 23% for diabetes [ 97 ]…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is one important aspect of function targeted during rehabilitation due to its association with hospital admission (8), risk of stroke (9), development of cardiovascular diseases (10,11), and mortality (12)(13)(14). Physical activity is easily measured using wearable devices (e.g., Fitbits); however, clinical utility is limited by the time required to set up the device, download and analyze data, and synthesize, document, and discuss the results (2,5,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%